Congenital Cutaneous Hemangioma in a Newborn Lamb - Alvarenga Nascimento, Karla; Alves Ferreira Júnior, Jair; Lourença de Souza, Verônica; Soto-Blanco, Benito; Lopes Câmara, Antônio Carlos; Targino Silva Almeida e Macêdo, Juliana; Pedroso, Pedro Miguel Ocampos (Acta Scientiae Veterinariae, 2022)
Background: Hemangioma is a benign dermal or subcutaneous endothelial cell tumor composed of vascular spaces of varying sizes filled with erythrocytes and lined with a single layer of uniform endothelial cells. Although the pathogenesis is not well defined, these tumors are considered to result from an imbalance in angiogenesis, leading to uncontrolled proliferation of vascular elements. To the best of our knowledge, there are no reports of congenital cutaneous hemangioma in sheep. This report describes the clinical, laboratory, and pathological findings of a case of congenital hemangioma affecting a newborn lamb. Case: A 5-day-old crossbred (Dorper x Santa Inês) lamb presenting with an ear nodule that expanded in the right ear was necropsied. An expansive subcutaneous nodule was observed macroscopically; it occupied approximately 90% of the right ear and had a crusty, irregular surface. The cut surface had multiple cavitations delimited by firm fibrous tissue and a light yellow-to-translucent content. Microscopically, it showed focally extensive subcutaneous neoplastic proliferation and moderate cellularity; it was formed of vascular beds of varied sizes and supported by moderate fibrocollagenous stroma. Suppurative inflammation was observed in the neoplastic vascular beds with large amounts of free basophilic coccoid bacteria inside macrophages. Immunohistochemistry analysis was performed to confirm the diagnosis. Strong cytoplasmic labeling was observed in neoplastic endothelial cells for CD31 and factor VIII. The Ki67 proliferation marker was positive in approximately 5% of neoplastic cells. The cells did not express smooth muscle actin (1A4) or pan-cytokeratin (AE1AE3). Histological characteristics and immunohistochemistry findings were consistent with those of congenital cutaneous hemangioma, a rare neoplasm in sheep. Discussion: The association of clinical, anatomopathological, and immunohistochemical data enabled the diagnosis of congenital cutaneous hemangioma in the 5-day-old lamb. Reports of vascular tumors in sheep are not frequent in literature and usually involve adult animals with no anatomical site predilection. In sheep, the occurrence of nasotracheal hemangioma in a 2-year-old ewe and gingival hemangioma in a 5-year-old sheep have already been described. A cutaneous extra-neural hemangioblastoma was diagnosed in the ear of a 1-month-old lamb. IHC was also used to confirm the diagnosis of hemangioblastoma. Macroscopically, hemangiomas can present as well-delimited and encapsulated masses that when cut, show a reticulated pattern similar to honeycombs that separate the blood-filled cavities. The present case showed a similar conformation but without enough erythrocytes to result in a bloody appearance. Tumor drainage and the predominance of blood serum in the content possibly made it macroscopically translucent. Microscopically, the hemangioma was classified as cavernous. This morphological variation forms large channels separated by fibrous connective tissue stroma, which may contain inflammatory cells. IHC confirmed the endothelial lining of the cystic cavities and was crucial in excluding differential diagnoses. Thus, factor VIII-related antigen was used as a marker for normal and neoplastic cells, as well as for tumoral and reactive neovascularization, in which neoplastic cells were immuno-expressed for CD31 and Factor VIII. In domestic animals, the association between CD31 and Factor VIII is considered more specific for vascular endothelial cells, differentiating them from cells of lymphatic origin. Congenital cutaneous hemangioma occurs in sheep, and its diagnosis and differentiation can be based on histopathology associated with conventional immunohistochemical panels for vascular neoformation. Keywords: sheep, mesenchymal neoplasm, vascular tumour, small ruminant, histopathology, immunohistochemistry.